Measuring Peripheral Chemoreflex Hypersensitivity in Heart Failure - Keir, Daniel A.; Duffin, James; Floras, John S. (Frontiers in Physiology, 2020)
Heart failure with reduced ejection fraction (HFrEF) induces chronic sympathetic activation. This disturbance is a consequence of both compensatory reflex disinhibition in response to lower cardiac output and patient-specific activation of one or more excitatory stimuli. The result is net adrenergic output that exceeds homeostatic need, which compromises cardiac, renal, and vascular function, and foreshortens lifespan. One such sympatho-excitatory mechanism, evident in ~40-45% of those with HFrEF, is augmentation of carotid (peripheral) chemoreflex ventilatory and sympathetic responsiveness to reductions in arterial oxygen tension and acidosis. Recognition of the contribution of increased chemoreflex gain to the pathophysiology of HFrEF and to patients’ prognosis has focused attention on targeting the carotid body to attenuate sympathetic drive, alleviate heart failure symptoms, and prolong life. The current challenge is to identify those patients most likely to benefit from such interventions. Two assumptions underlying contemporary test protocols are: that the ventilatory response to acute hypoxic exposure quantifies accurately peripheral chemoreflex sensitivity, and that the unmeasured sympathetic response mirrors the determined ventilatory response. This Perspective questions both assumptions, illustrates the limitations of conventional transient hypoxic tests for assessing peripheral chemoreflex sensitivity, and demonstrates how a modified rebreathing test capable of comprehensively quantifying both the ventilatory and sympathoneural efferent responses to peripheral chemoreflex perturbation, including their sensitivities and recruitment thresholds, can better identify individuals most likely to benefit from carotid body intervention.